The Effect of Compensation, Empowerment, Competency and Job Satisfaction toward Performance of Lecture in Wiralodra Universiti of Indramayu - Hr., Sumardi; Dr.Wibowo, Prof. (International Journal of Scientific Research and Management (IJSRM), 2018)
The performance of UNWIR lecturers has not been fully in line with the expectations. Achievement of lecturer performance at UNWIR is quite good category. This study aims to determine the effects resulting from compensation, empowerment, competence on job satisfaction and compensation, empowerment, competence and job satisfaction on the performance of UNWIR lecturers. The method used in this study is quantitative associative that 104 respondents of UNWIR lecturers are assigned. The data was collected by using performance appraisal instrument by chairman of UNWIR and lecturer response instrument relating to the compensation, empowerment, competence and job satisfaction of UNWIR lecturer. Data processing were analyzed using path analysis by LISREL 9.30 software. The result showed that performance appraisal of lecturers of UNWIR by chairman of UNWIR is quite less / low category, response of lecturer on compensation received is sufficient, the empowerment done by UNWIR to the lecturer is enough and the competency assessment of each lecturer are respectively in the good category, the perceived job satisfaction Lecturers are in the category of satisfaction and overall there is a significant relationship between compensation, empowerment and competence on job satisfaction and there is a relationship between compensation, empowerment, competence and job satisfaction on performance..